2021
DOI: 10.1093/eurpub/ckab103
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing measures: barriers to their implementation and how they can be overcome – a systematic review

Abstract: Background Despite their central role in the global response to the COVID-19 pandemic and previous infectious disease outbreaks, factors influencing the acceptability and implementation of social distancing measures are poorly understood. This systematic review aims to identify such factors drawing on qualitative literature. Methods A systematic search was carried out in eleven databases. Papers were included in the review if… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
(235 reference statements)
2
16
0
1
Order By: Relevance
“…The clinical evidence accumulated so far would hence suggest that older people should be especially protected from SARS-CoV-2 infection. Nonetheless, physical measures such as wearing face mask, social distancing, hand hygiene and so forth are only partially effective for preventing viral infection and COVID-19-related complications [ 7 ], so that widespread administration of COVID-19 vaccines is now regarded as the most effective preventive strategy in older persons [ 8 ], as already proven for other infectious diseases such as influenza, meningococcal and pneumococcal diseases, hepatitis, herpes zoster, diphtheria and tetanus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical evidence accumulated so far would hence suggest that older people should be especially protected from SARS-CoV-2 infection. Nonetheless, physical measures such as wearing face mask, social distancing, hand hygiene and so forth are only partially effective for preventing viral infection and COVID-19-related complications [ 7 ], so that widespread administration of COVID-19 vaccines is now regarded as the most effective preventive strategy in older persons [ 8 ], as already proven for other infectious diseases such as influenza, meningococcal and pneumococcal diseases, hepatitis, herpes zoster, diphtheria and tetanus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been found to predict adherence to social distancing and other protective practices against COVID-19. For example, Sadjadi et al ( 40 ) found that communication and support were the strongest enablers of social distancing from an institutional perspective. Without neglecting the interaction of agents and institutions, the temporal discounting perspective of the present study takes a different stance than other psychological and social factors insofar as it considers primarily the relation between the agent and his or her future self.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of research examining barriers to the implementation of social distancing measures implemented during COVID-19 uncovered two categories of barriers: individual-psychological/psychosocial and sociological phenomena, and shortcomings in governmental action or communication. Specific psychological and psychosocial barriers revealed include avoiding stigma, feelings of solidarity, perceived threat and value of the intervention, and alignment of messaging and lived experience, accounting for life circumstances and addressing social norms [ 27 ]. Government factors included providing support for people to adhere to social distancing mandates and trust in government, and involving the community in both the pandemic’s planning and response phase [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific psychological and psychosocial barriers revealed include avoiding stigma, feelings of solidarity, perceived threat and value of the intervention, and alignment of messaging and lived experience, accounting for life circumstances and addressing social norms [ 27 ]. Government factors included providing support for people to adhere to social distancing mandates and trust in government, and involving the community in both the pandemic’s planning and response phase [ 27 ]. The factors that are associated with either the inability or unwillingness to comply with stay-at-home mandates seem more closely related to socioeconomic marginalization (SEM).…”
Section: Introductionmentioning
confidence: 99%